Association Between Pre-operative BUN and Post-operative 30-Day Mortality in Patients Undergoing Craniotomy for Tumors: Data From the ACS NSQIP Database - Liu, Yufei; Hu, Haofei; Li, Zongyang; Han, Yong; Chen, Fanfan; Zhang, Mali; Li, Weiping; Huang, Guodong; Zhang, Liwei (Frontiers in Neurology, 2022)
Objective: There is limited evidence to clarify the specifc relationship between preoperative blood urea nitrogen (BUN) and postoperative 30-day mortality in patients undergoing craniotomy for tumors. Therefore, we aimed to investigate details of this relationship. Methods: Electronic medical records of 18,642 patients undergoing craniotomy for tumors in the ACS NSQIP from 2012 to 2015, were subject to secondary retrospective analysis. The principal exposure was preoperative BUN. Outcome measures were postoperative 30-day mortality. We used binary logistic regression modeling to evaluate the association between them, and conducted a generalized additive model and smooth curve fitting (penalized spline method) to explore the potential relationship and its explicit curve shape. We also conducted sensitivity analyses to ensure the robustness of the results, and performed subgroup analyses. Results: A total of 16,876 patients were included in this analysis. Of these, 47.482% were male. The postoperative 30-day mortality of the included cases was 2.49% (420/16,876), and the mean BUN was 16.874 ± 6.648 mg/dl. After adjusting covariates, the results showed that preoperative BUN was positively associated with postoperative 30-day mortality (OR=1.020, 95% CI: 1.004, 1.036). There was also a non-linear relationship between BUN and postoperative 30-day mortality, and the inflection point of the BUN was 9.804. For patients with BUN < 9.804 mg/dl, a one unit decrease in BUN was related to a 16.8% increase in risk of postoperative 30-day mortality (OR=0.832, 95% CI (0.737, 0.941); for patients with BUN > 9.804 mg/dl, a one unit increase in BUN was related to a 2.8% increase in risk of postoperative 30-day mortality (OR=1.028 , 95% CI (1.011, 1.045). The sensitivity analysis proved that the results were robust. The subgroup analysis revealed that all listed subgroups did not affect the relationship between preoperative BUN and postoperative 30-day mortality (P > 0.05). Conclusion: Our study demonstrated that preoperative BUN (mg/dl) has specific linear and nonlinear relationships with postoperative 30-day mortality in patients over 18 years of age who underwent craniotomy for tumors. Proper preoperative management of BUN and maintenance of BUN near inflection point (9.804 mg/dl) could reduce risk of postoperative 30-day mortality in these cases.